PENGARUH FASILITAS BELAJAR DARI ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI SMP NEGERI 3 TELUK KUANTAN KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Nurmaslina '; Gimin '; Supentri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the problems that arise from the observations made by the researcher is the low motivation of student learning due to lack of learning facilities provided by parents to their children. The formulation of the problem in this research is (1) how student learning motivation in SMP NEGERI 3 Teluk Kuantan The Distric Kuantan Tengah Kuantan Singingi Regency (2) how study facilities from parents in SMP NEGERI 3 Teluk Kuantan The Distric Kuantan Tengah Kuantan Singingi Regency (3) The influence of learning facilities from parents on student learning motivation in SMP NEGERI 3 Teluk Kuantan The Distric Kuantan Tengah Kuantan Singingi Regency. The purpose of this study is to explain and analyze the learning facilities of parents, students' learning motivation and the influence of learning facilities from parents to student learning motivation in SMP NEGERI 3 Teluk Kuantan The Distric Kuantan Tengah Kuantan Singingi Regency. This research method is descriptive quantitative. The data collection instrument used in this research is a questionnaire consisting of 13 statements about parent learning facilities (variable X) and 17 statements about learning motivation (variable Y). These data were analyzed using simple linear regression. Thus the hopotesis which states